Virginia Woolf's novels and the literary past - De Gay, Jane, 1966- (Edinburgh University Press, 2006)
This is the first book to explore Virginia Woolf's preoccupation with the literary past and its profound impact on the content and structure of her novels. It analyses Woolf's reading and writing practices via her essays, diaries and reading notebooks and presents chronological studies of eight of her novels, exploring how Woolf's intensive reading surfaced in her fiction. The book sheds light on Woolf's varied and intricate use of literary allusions; examines ways in which Woolf revisited and revised plots and tropes from earlier fiction; and looks at how she used parody as a means both of critical comment and homage. Key Features The first book-length study of intertextuality in Virginia Woolf's novels Offers a challenging and provocative new perspective on Woolf's art as a novelist Develops detailed close readings offering fresh insights into individual works Presents complex ideas in a lucid and accessible fashion